2020
DOI: 10.1183/23120541.00529-2020
|View full text |Cite
|
Sign up to set email alerts
|

The DIAMORFOSIS (DIAgnosis and Management Of lung canceR and FibrOSIS) survey: international survey and call for consensus

Abstract: BackgroundCurrently there is major lack of agreement on the diagnostic and therapeutic management of patients with Idiopathic Pulmonary Fibrosis (IPF) and lung cancer (LC). Our aim was to identify variations in diagnostic and management strategies across different institutions and provide rationale for a consensus statement on this issue.MethodsThis was a joint-survey by ERS Assemblies 8, 11 and 12. The survey consisted of 25 questions.ResultsFour hundred ninety four (n=494) physicians from 68 different countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 39 publications
0
36
0
1
Order By: Relevance
“…Tzouvelekis et al, in 102 patients with IPF and lung cancer from a multicenter in Greece, reported that SqCC (34.3%) was the most common histologic subtype 35 . However, in a recent international survey performed by the ERS, participating physicians responded that adenocarcinoma (58.6%) was the most common histological type of lung cancer in patients with IPF, followed by SqCC (26.6%) 36 . In addition, the high proportion of male patients and lower lobe predominance are consistent with the results of previous studies 14 , 16 , 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tzouvelekis et al, in 102 patients with IPF and lung cancer from a multicenter in Greece, reported that SqCC (34.3%) was the most common histologic subtype 35 . However, in a recent international survey performed by the ERS, participating physicians responded that adenocarcinoma (58.6%) was the most common histological type of lung cancer in patients with IPF, followed by SqCC (26.6%) 36 . In addition, the high proportion of male patients and lower lobe predominance are consistent with the results of previous studies 14 , 16 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there were no differences in survival between the IPF and no-IPF groups among patients with SCLC or advanced (stage IV) NSCLC. A recent international survey reported that palliative care (69%) was the most frequent management in both advanced IPF and lung cancer (TNM stage IV) cases 36 . However, Koyama et al, in 122 patients with SCLC, reported that the IPF group (n = 20, median survival 244 days) had shorter survival than the IIP (idiopathic interstitial pneumonia) other than IPF group (n = 27, median survival 386 days) or non-IIP group (n = 73, median survival 592 days, P = 0.001) 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Platinhaltige Zweifach-Chemotherapie-Schemata und Immuntherapie bei metastasierter Erkrankung wurden von 25% bzw. 32% der Befragten angegeben [162].…”
Section: Lungenkrebsunclassified
“…aspiration/biopsy (EBUS-TBNA/B) 19 . On the contrary, agreement rates were considerably decreased in cases of severe IPF 19 .…”
Section: A B Cmentioning
confidence: 99%
“…Current American Thoracic Society (ATS), European Respiratory Society (ERS), Japanese Respiratory Society (JRS) and Latin American Thoracic Society (ALAT) guidelines do not address this crucial issue 1,7 . A recently published international survey, denominated the DIAMORFOSIS (DIAgnosis and Management Of lung canceR and FibrOSIS) survey, identified major heterogeneity in diagnostic and management strategies across different institutions and highlighted the amenable need for a consensus statement 19 . This review article aims to address the main diagnostic and therapeutic challenges for patients with IPF and lung cancer through a Q (questions) and A (answers) approach.…”
Section: Introductionmentioning
confidence: 99%